Just for the Money:: circus lives and contemporaneity - de la Riva, Germán; Iribarren Muñoz, Itsaso (Revista Brasileira de Estudos da Presença, 2025)
This article analyzes circus life as a model of adaptation to the tensions of contemporary life, characterized by the increasing dissolution of the boundaries between the work and personal spheres. Through the knowledge passed down from generation to generation in the circus tradition, we examine how this space configures practical tools to face uncertainty. Likewise, the art of circus, through its everyday patterns of communication and comprehension of the environment, is positioned as a critical questioning of traditional narratives about work, community and belonging, and at the same time it is proposed as a representative example of emerging ways of life.